Physical Activity and Nutrition-Related Beliefs, Behaviors, and Challenges in Individuals Living With Cancer and Their Caregivers. Issue 1 (15th August 2022) - Packel, Lora; Dychtwald, Dan; Pontiggia, Laura; Deutsch, Jonathan; Milliron, Brandy-Joe
Abstract : Background and Purpose: This study explored physical activity and nutrition beliefs, behaviors, and challenges; examined dyadic interactions; and explored lifestyle programming preferences to inform future interventions to improve the physical and mental health of patients with cancer and their caregivers. Methods: A convergent mixed-methods design with structured surveys and interviews. Descriptive statistics and quantitative comparisons were performed using SAS. Interviews were analyzed using inductive and deductive thematic analysis. Setting: Hope Lodge Cheltenham, Pennsylvania. Participants: Caregivers (n = 52) and patients (n = 50). Intervention and Measurements: The Godin Leisure Time Questionnaire, theory of planned behavior, and the National Cancer Institute's Food Attitudes and Behaviors Survey were embedded in structured surveys. Results: The sample was physically active with no significant changes postdiagnosis. Physical activity was lower in patients with higher fatigue, while it was higher in those with stronger intention and perceived behavioral control. Most participants believed that dietary intake was linked to health; however, there was confusion toward national recommendations. Higher levels of nutrition self-efficacy were associated with lower perceived barriers to nutrition in both groups. Participants wanted information tailored to cancer type provided in a variety of mediums by health care providers, researchers, and cancer centers. Limitations: Physically active sample of convenience, recall bias with questionnaires. Conclusions: Perceived behavioral control, intention to exercise, and education about using exercise for fatigue management and mental health should be emphasized. Nutrition interventions should focus on addressing barriers, clarifying guidelines, and operationalizing recommendations. Information should be specific to cancer type and include support for caregivers.